2019
DOI: 10.1177/1352458519834857
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of conventional MRI parameters in first spinal attacks of neuromyelitis optica spectrum disorder

Abstract: Background: While spinal cord (SC) attacks of neuromyelitis optica spectrum disorder (NMOSD) are often devastating, signs predictive of their poor clinical outcome have been elusive until now, except for the delay in initiating plasma exchange (PE). Objective: We studied the correlation between conventional non-standardized magnetic resonance imaging (MRI) parameters, PE treatment, and clinical data obtained at nadir and recovery. Methods: Retrospective study of first SC attacks of NMOSD. Results: Sixty-nine A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
5
1
Order By: Relevance
“…The length of spinal lesions is correlated with inflammatory activity and neurological impairment (21,37) and is correlated with disease severity based on the admission EDSS score (38,39). Our study demonstrated for the first time that RGMa levels were positively correlated with the length of spinal lesions on NMOSD MRI scans.…”
Section: Discussionsupporting
confidence: 50%
“…The length of spinal lesions is correlated with inflammatory activity and neurological impairment (21,37) and is correlated with disease severity based on the admission EDSS score (38,39). Our study demonstrated for the first time that RGMa levels were positively correlated with the length of spinal lesions on NMOSD MRI scans.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, univariate analysis showed that spinal cord MRI showing LETM had a moderate influence on the initial EDSS score and prognosis of NMOSD, but there was no significant correlation in multivariate analysis, and previous studies have found that the length of spinal cord lesions is related to the initial severity of the disease and residual disability (59). The ability of MRI parameters to predict NMOSD prognosis requires further exploration.…”
Section: Discussioncontrasting
confidence: 45%
“…Women with NMOSD have a higher percentage of pregnancy loss than expected for age. 52 Additional clinical factors that have been associated with increased relapse risk or worse disability include brainstem-onset attacks, 47,53 longer length of myelitis lesions, 33,54 optic neuritis at disease onset, 55 and severity of initial attack. 45,49 There does not seem to be a correlation between outcomes and gadolinium enhancement of CNS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…45,49 There does not seem to be a correlation between outcomes and gadolinium enhancement of CNS lesions. 54 As far as serologic testing, the titer of AQP4-IgG has not been shown to correlate with disease severity or prognosis. 56 However, in comparison with MOG antibody disease, AQP4-Ab positive and double seronegative NMOSD correlate with worse disability.…”
Section: Discussionmentioning
confidence: 99%